2022
DOI: 10.3390/su14094874
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Impact of the Perceived Value of Public on Panic Buying Behavior during COVID-19

Abstract: In this paper, an evolutionary game model for the development of panic buying events in COVID-19 is constructed by studying the dynamic process of the public and the government adjusting their strategic choices and playing a continuous game. This paper uses regret theory to depict the public’s perceived value of the items in the panic buying situation, describes the characteristics of each stage of the rumors spreading process and the evolution process of panic buying events, and introduces the variable of pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…When there are no clear guidelines or restrictions in place, individuals may feel a sense of uncertainty and insecurity, leading to a heightened sense of panic and a rush to stockpile essential goods. (Mao et al, 2022) Stringent Government Control: Conversely, when the government implements strict control measures, such as lockdowns or rationing systems, panic buying may be reduced. Clear and decisive government actions can provide a sense of security and stability, assuring the public that the necessary measures are being taken to manage the crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When there are no clear guidelines or restrictions in place, individuals may feel a sense of uncertainty and insecurity, leading to a heightened sense of panic and a rush to stockpile essential goods. (Mao et al, 2022) Stringent Government Control: Conversely, when the government implements strict control measures, such as lockdowns or rationing systems, panic buying may be reduced. Clear and decisive government actions can provide a sense of security and stability, assuring the public that the necessary measures are being taken to manage the crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cooper and Gordon (2021) observed that in response to COVID-19, due to the possible future shortage of resources there was an increase in panic buying in the early 2020s. To mitigate the negative effects of crisis on the NDGs industry in the future, governments at all levels could introduce policies discouraging misinformation, they should consistently provide updates on industries and disincentivise rumours (Mao, Hou, & Xie, 2022).…”
Section: Implications For Theory and Policymentioning
confidence: 99%
“…Significant endeavors have been dedicated to unraveling the intricacies of panic buying and comprehending the factors shaping this phenomenon. Numerous studies have approached panic as a psychological response, focusing on pinpointing the contributing factors to such reactions [ 12 , 13 , 14 ]. Some researchers have also investigated how panic can disrupt the equilibrium between supply and demand [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%